Deposition of Micro Contact Based Probe Cell for IC Testing by Dc Magnetron Sputtering Technique - Muhammad Idzdihar , Idris; Nowshad , Amin; Faiz , Arith; Siti Amaniah, Mohd Chachuli (Maxwell Scientific Publications, 2014)
This study presents the deposition of micro contact probe cell for IC testing deposited by dc sputtering technique on a glass substrate. Micro contact with thickness of 2800-7000 nm were deposited from Copper target at sputtering power of 125 W in argon ambient at a room temperature on a base layer of copper using mask. Then, the micro contacts were investigated by using profilometer. All the obtained results show the potential viability of the novel test fixture and thus solve the limitation